Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Optimising light intensity and ammonium enrichment enhances ex-situ growth and survival of the cultured boring Giant clam, Tridacna crocea - Li Keat Lee; Teresa S. Tay; H.R. Samuel Lee; K.E. Kayden Tong; M.Y. Beryl Chean; Yuchen Sun; Mei Lin Neo (Aquaculture, 2026)

Accumulation of microplastics in various organs of fiddler crabs and sea cucumbers across the coastal habitats in Singapore - Jenny Fong; Ashwini Suresh Kumar; Zhen Yu Choy; Yi Hong Tan; Jasmine Anya Putri Gowidjaja; Mei Lin Neo (Environmental Pollution, 2025)

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

First success in captive breeding of the Tiger Cowrie, Cypraea tigris (Gastropoda: Cypraeidae), with notes on its early life development - Teresa S. Tay; K.E. Kayden Tong; Yuchen Sun; Mei Lin Neo (Molluscan Research, 2024)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Genome skimming resolves the giant clam (Bivalvia: Cardiidae: Tridacninae) tree of life - Edwin Y. W. Tan; Z. B. Randolph Quek; Mei Lin Neo; Cécile Fauvelot; Danwei Huang (Coral Reefs, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

A preliminary investigation of epibiotic macrofauna on the mangrove horseshoe crab Carcinoscorpius rotundicauda (Latreille, 1802) in Singapore - LIM Chin Sing; TAN Lester Jin Xiang; NEO Mei Lin; TEO Serena Lay Ming; BENG Stephen Sui Leung; NADARAJAN Saravanan; TUN Karenne (Marine Biology Research, 2021)

Diversity of endosymbiotic Symbiodiniaceae in giant clams at Dongsha Atoll, northern South China Sea - Sherlyn Sher Qing Lim; Danwei Huang; Keryea Soong; Mei Lin Neo (Symbiosis, 2019)

Drastic decline in giant clams (Bivalvia: Tridacninae) around Mauritius Island, Western Indian Ocean: implications for conservation and management - Sundy Ramah; Nawsheen Taleb-Hossenkhan; Peter A. Todd; Mei Lin Neo; Ranjeet Bhagooli (Marine Biodiversity, 2019)

DNA barcoding of traded shark fins, meat and mobulid gill plates in Singapore uncovers numerous threatened species - Benjamin J. Wainwright; Yin Cheong Aden Ip; Mei Lin Neo; Jia Jin Marc Chang; Chester Zhikai Gan; Naomi Clark-Shen; Danwei Huang; Madhu Rao (Conservation Genetics, 2018)

First observations of Tridacna noae (Röding, 1798) (Bivalvia: Heterodonta: Cardiidae) in Christmas Island (Indian Ocean) - Mei Lin Neo; Jeffrey K. Y. Low (Marine Biodiversity, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Dichromatism in the commensal shrimp Anchistus miersi (De Man, 1888) - Mei Lin Neo; Bee Yan Lee; Kareen Vicentuan; Peter Alan Todd (Marine Biodiversity, 2015)

Quantification of water squirting by juvenile fluted giant clams (Tridacna squamosa L.) - Mei Lin Neo; Peter Alan Todd (Journal of Ethology, 2011)

Can artificial substrates enriched with crustose coralline algae enhance larval settlement and recruitment in the fluted giant clam (Tridacna squamosa)? - Mei Lin Neo; Peter A. Todd; Serena Lay-Ming Teo; Loke Ming Chou (Hydrobiologia, 2009)